A psychological perspective on immigration: the reasons and hardships of migrating to Brazil's capital, Brasília. Issue 3 (12th September 2016) - Carvalho, Alberto Rodrigues; Martins, Francisco Catunda
Abstract : Purpose: The purpose of this paper is to seek the inner motivations present in immigrants moving from different regions of Brazil to its capital, Brasília. The goal is to find out the individuals' stories, not only the macroeconomic aspects usually studied in migration movements. Also, the authors intend to understand how impacting the process of leaving one's homeland and loved ones behind can be. Design/methodology/approach: In this study, ten recent immigrants were interviewed about their inner motivations to migrate to Brasília and the difficulties faced. Their answers were categorized and distributed into charts showing the most relevant parts for the study. Findings: Two main topics stood out: work and love. The search for a meaningful and rewarding job is a strong enough reason to migrate. Love presents itself as a different reason to migrate, especially when economic and political reasons are the most common motivators. Love has to do with wanting to be with a partner or family. Migration is a time for crisis, mourning can be present and the strangeness of the new place may affect some more than others. All interviewees mentioned the hardships of adapting, be it emotionally or psychologically. Originality/value: It is a response to the lack of clinical psychology studies about migration in Brazil. The importance of having studies carried out with a more qualitative perspective in the field of migration, in which the focus are the inner motivations of the migrants and what their experiences are.